Abortion Due to Fetal Defects (Legal Analysis of Legislation and Fatwa of Ulama Mufti Bayan Linnas Number 68): Aborsi Karena Cacat Janin (Analisis Hukum Terhadap Peraturan Perundangan dan Fatwa Ulama Mufti Bayan Linnas Nomor 68) - Abdullah, Arifin; Binti Hassan, 'Affaf (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Abortion is a word that symbolizes a crime in which the perpetrator must be punished because it is considered to have taken away a human being's right to life. However, sometimes abortion has to be carried out because if the pregnancy continues, the mother's life will be at stake due to the disability suffered by the occupant of her womb. Defects experienced by the fetus must be declared by a recognized medical expert in the field of pregnancy. This research question is how the laws and fatwas from Malaysian mufti clerics conclude the legal status of abortion due to fetal defects. In this research the author uses library research methods and is normative juridical in nature. Malaysia does not have specific laws governing abortion, so everything related to abortion will refer to Penal Code Section 312-316 (Act 574). Dr. Zulkifli Mohamad Al-Bakri, former Minister of Religion and Mufti of the 7th Federal Region stated in an article uploaded to Bayan Linnas No. 68 states that abortion is divided into two laws, namely mandatory if it has not reached the age of 120 days and haram if it has reached the age of 120 days or more unless the fetus being impregnated threatens the mother's life then it is permitted. Here it can be concluded that abortion is permitted if there is harm to the mother. If there is no harm, it is prohibited and forbidden.